Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4236/ce.2021.127114
|View full text |Cite
|
Sign up to set email alerts
|

Digital Learning among Postgraduate Students in the Times of COVID-19: A Literature Review

Abstract: COVID-19, as a global pandemic has caused a dramatic change in the education landscape. With significant policies such as social distancing and movement restrictions, all educational institutions have been shut to flatten the curve. As a response to the unprecedented crisis, digital learning has been given rise to pushing behind conventional classes from primary to tertiary levels. The adoption of online lessons and digital classrooms has mechanized a new pattern of teaching and learning mediated by today's ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This was mainly influenced by isolation, loneliness, and worry about getting sick (Ihm et al, 2021). The conducted research analysis showed that the most common challenges postgraduate students face are technological difficulties, health, and lack of interaction (Seladorai & Mohamed, 2021). According to Ayebi-Arthur (2017), strong IT infrastructure is a prerequisite for online learning.…”
Section: Discussionmentioning
confidence: 99%
“…This was mainly influenced by isolation, loneliness, and worry about getting sick (Ihm et al, 2021). The conducted research analysis showed that the most common challenges postgraduate students face are technological difficulties, health, and lack of interaction (Seladorai & Mohamed, 2021). According to Ayebi-Arthur (2017), strong IT infrastructure is a prerequisite for online learning.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al (2021) highlight the technical problems related to computer and smart-phone management as a barrier to digital education. Seladorai and Mohamed (2021) put their concluding remarks saying that "the significance of understanding and addressing students' barriers in embracing digital learning such as technology, health and lack of interaction will propel the splendid side of digital learning". However, Khan et al (2021) state that "online education results are not always a boon for the educational community as they pose many opinions in the context of online teaching and learning, leading to widespread concern over the controversial issue of teaching education" (p. 442).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the isolation resulting from the COVID-19 outbreak has exacerbated mental health issues among college students [ 41 ]. In response to the spread of the COVID-19 pandemic, many institutions have adopted major policies such as social distancing and movement restrictions, and all educational institutions have been closed for an extended period [ 42 ]. Moreover, the shift from offline learning to prolonged online learning brings in a lot of stress and anxiety, all of which have a serious impact on the mental health of college students.…”
Section: Introductionmentioning
confidence: 99%